Analisis Pustaka Tentang Hubungan Metode Penilaian Kreatif dan Minat Belajar Siswa dalam Sejarah Kebudayaan Islam - Rabbiatul Alawiyah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study discusses the relationship between creative assessment and students' interest in learning Islamic Cultural History (SKI). Creative assessments, such as projects, portfolios, and simulations, offer a more engaging approach and encourage active student engagement than conventional methods. Through literature analysis, this study examines the concept of creative assessment, indicators of learning interest, and its application in SKI learning. The results of the study show that creative assessment is able to increase students' interest in learning by creating a dynamic and relevant learning atmosphere. In the context of SKI, methods such as historical dramas and visual projects help students understand Islamic values in depth while also increasing enthusiasm for the material. The conclusion of this study reveals a positive relationship between creative assessment and students' interest in learning, which contributes to the effectiveness of SKI learning.